2018
DOI: 10.1016/j.jsat.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medication assisted treatment (MAT) for opioid use disorder on functional outcomes: A systematic review

Abstract: This systematic review synthesizes evidence on the effects of Medication-Assisted Treatment (MAT) for opioid use disorder (OUD) on functional outcomes, including cognitive (e.g., memory), physical (e.g., fatigue), occupational (e.g., return to work), social/behavioral (e.g., criminal activity), and neurological (e.g., balance) function. Five databases were searched from inception to July 2017 to identify English-language controlled trials, case control studies, and cohort comparisons of one or more groups; cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 64 publications
0
46
0
5
Order By: Relevance
“…Fifty-eight percent (14/24) of systematic reviews on pharmacological interventions included studies which reported housing instability or homelessness [41,42,44,46,50,51,53,[55][56][57][58][59][60]64]. All systematic reviews on SCFs included observational studies reporting the rate of The effectiveness of substance use interventions for homeless and vulnerably housed persons homelessness ranging from 10% to as high as 75% among SCF clients, the majority of studies were from Sydney, Australia and Vancouver, Canada [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-eight percent (14/24) of systematic reviews on pharmacological interventions included studies which reported housing instability or homelessness [41,42,44,46,50,51,53,[55][56][57][58][59][60]64]. All systematic reviews on SCFs included observational studies reporting the rate of The effectiveness of substance use interventions for homeless and vulnerably housed persons homelessness ranging from 10% to as high as 75% among SCF clients, the majority of studies were from Sydney, Australia and Vancouver, Canada [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…Methadone was associated with more adverse events compared to buprenorphine, including sedation [50,60], but not compared to slow release oral morphine (81% SROM vs 79% methadone, p = 0.62 [no further data reported]) [63]. Buprenorphine patients had a significantly lower prevalence of fatigue (15.5% vs 25.1%; risk ratio 0.62; 95% CI 0.41-0.95; GRADE certainty of evidence [as reported in [64]: moderate) but no difference in insomnia (risk ratio1.12 95%CI 0.78-1.62) compared to methadone patients [64].…”
Section: Pharmacological Interventions For Opioid Use Disordermentioning
confidence: 99%
“…Some report neurocognitive performance that does not differ from abstinent former heroin users or controls; however, others have found impairment in episodic memory, psychomotor speed, working and long-term memory, decision-making, and response inhibition [55]. A systematic review examined the effects of opioid substitution therapy (i.e., methadone and buprenorphine treatment) on cognitive function [56]. Compared to healthy controls, individuals taking either medication displayed worse performance in working memory (i.e., number sequencing tasks), with no significant difference found between methadone and buprenorphine users [57].…”
Section: Medication Assisted Treatmentmentioning
confidence: 99%
“…Currently, there are three approved medications for the treatment of opioid addiction, including methadone, buprenorphine, and naltrexone (McElrath 2018;Maglione et al 2018;Herring et al 2019;Blanco and Volkow 2019) (Table 1). Buprenorphine, for example, has been quite effective in randomized clinical trials (Herring et al 2019;Gowing et al 2017) for managing acute symptoms during the detoxification and maintenance phases of opioid addiction treatment.…”
Section: Introductionmentioning
confidence: 99%